Flexible, Multi-phased Hotel Development. (2015) - Milwicz, Roman; Dubas, Sebastian
Abstract: There is a need for diverse development strategy considering risks of investing in the hospitality market adequate for time varying market requirements. Implementation of long-term investments based on assumptions and forecasts causes a high risk of loss. The target is to find solutions preventing risks and seizing opportunities. In a case study hotel expansion is planned therefore different scenarios were analysed. Historical data enable prediction of market changes; as a result spectrum of demand for services was created. Standard and flexible approach to selected scenarios was analysed with emphasis on development of investment process, minimize risk and optimize profit.